Penelusuran Kebutuhan Secara Apresiatif (Appreciative Inquiry) di Unit Pemukiman Transmigrasi Kolikapa Kecamatan Maukaro Kabupaten Ende Provinsi Nusa Tenggara Timur - Kharis Ragil Triyanto; Dwi Putra Darmawan; I Putu Gde Sukaatmaja (Universitas Udayana, 2016)
Transmigration Settlement Unit (UPT) Kolikapa Maukaro District Ende Regency of East Nusa Tenggara Province is one of the residential units are still relatively new and has not carried out the needs assesment. Today developed the concept of a needs analysis based on the potential to be developed in transmigration sites on the basis of dreams and potentials (Strength Based Solving). Based on this concept, people are asked to choose the skills based on the needs. So we get the training priority list, agenda development, and to support programs and regional development, social innovation is required. In turn in the future could increase the income of citizens. Based on the results of research using fast-research, in-depth interviews, direct observation and analysis of the results of the workshop, the obtained results of the type of training required (Training Needs/TN) is a health cadres, intensification yards, cultivation of horticultural crops, cultivation of poultry, small livestock, livestock large, community development and empowerment, agricultural processing cocoa, business groups, management of water and environmental health, handicrafts and weaving ikat, and entrepreneurship. Results of development needs (Development Needs/DN) are obtained, namely the rebuilding of the bridge connecting the village with the districts, additions and repairs piping clean water, seek electrical installation as a supporting ease the spread of information. In addition to the type of training and development agenda needs results obtained are also social innovation, which is building a village barn to control the current low price of rice harvest, to make regulations to control the village agricultural land conversion, coordinate with related agencies in community development. The present study included a suggestion to the motivator nongovernmental organizations to continue exploring the science, especially concerning the needs assesment. Results of assesments are appreciative requirement that can be used as a basis for community mobilization and also for the construction of the target communities. To the policy makers in handling the training community, they can continue to refine the search needs as the basis for the convening of community empowerment. Ensuring the availability of funds, resources, and supporting infrastructure needs of search activity.